2008
DOI: 10.1063/1.3021097
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation-induced plastic deformation and fracture behavior difference between a- and c-domains of BaTiO3 single crystal

Abstract: The plastic deformation and fracture behavior of individual a- and c-domains of (001) oriented BaTiO3 single crystal are studied with nanoindentation and atomic force microscopy. Consistent with previous observations in rocksalt and perovskite crystals, square-shaped pileups directly surround the residual indents, and rosette arm patterns extend beyond these pileups. These features have been ascribed to dislocation activities on the {110}⟨11¯0⟩ slip systems induced by nanoindentations. We observed rosette scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We performed nanoindentation experiments on two materials. The first one is (001) oriented BaTiO 3 single crystal (5 Â 5 Â 1 mm) (Sun and White (2008)), and the second one is quartz single crystal (z-cut, 10 Â 10 Â 0.5 mm)-both obtained from MTI Corporation, Richmond, CA. Quartz is expected to have negligible flexoelectricity (at least compared to BaTiO 3 ) and thus was chosen to provide a benchmark.…”
Section: Indentation Experimentsmentioning
confidence: 99%
“…We performed nanoindentation experiments on two materials. The first one is (001) oriented BaTiO 3 single crystal (5 Â 5 Â 1 mm) (Sun and White (2008)), and the second one is quartz single crystal (z-cut, 10 Â 10 Â 0.5 mm)-both obtained from MTI Corporation, Richmond, CA. Quartz is expected to have negligible flexoelectricity (at least compared to BaTiO 3 ) and thus was chosen to provide a benchmark.…”
Section: Indentation Experimentsmentioning
confidence: 99%
“…In addition, dislocations were not observed in PZT blocks during compression. While during nanoindentation, the indentation depth are thought to be mainly caused by dislocations [ 32 37 ], and the effect of domain reorientation on the indentation depth is limited. Since the dislocation initiation became easier with the help of thermal activation at high temperature [ 38 ], the indentation depth increases with increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that in BaTiO 3 crystal, both dislocation initiation and domain switching happened during indentation [ 32 37 , 46 ]. Since domain switching can also induce deformation in ferroelectrics, a part of the indentation depth is thought to be caused by domain reorientation during loading [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…the elastic modulus, E, and mean contact pressure, P m . As it was mentioned before, in nanoindentation tests the theoretical strength approach prior to the first pop-in event is correlated with the creation of dislocation sites required for the onset of plasticity [11,24]. Therefore, in order to determine the yields stresses, the occurrences of pop-in events were carefully identified in the nanoindentation P-h curves for the (001) BaTiO 3 single crystal.…”
Section: Analysis Of the P-h Curvesmentioning
confidence: 99%
“…Compared to other ferroelectrics material, like bismuth titanate-based ceramics Bi 3.96 Ce 0.04 Ti 3−x W x Nb x O 12 [7], barium titanate (BaTiO 3 ) is a crystal with a simple structure and easy to grow [8], therefore, it is a good candidate to understand the origin of the observed anisotropic properties [9]. The study of BaTiO 3 has given important information about the domains behavior formed on the surface of the material under mechanical stress [10,11]. Experimental observations found that domain switching in a ferroelectric ceramic is initially localized at the top and bottom surfaces, and then sweeps across the entire material, analogous to the movement of a dislocation [12].…”
Section: Introductionmentioning
confidence: 99%